(untitled) (GENDER EQUALITY: International Journal of Child and Gender Studies, 2019)
This paper aims to study child protection in Islamic law perspective, and how the perspective has derived into the Qanun Aceh on child protection. Islamic law discusses child protection as child nurture/safeguards (hadhanah) and custodian (walayah). Child protection means fulfilling children’s rights and protection from the harmful situation or things that could be a danger to their physics, soul, and property. On the national level, the Indonesian government stipulated the Undang-Undang Number 35 Year 2014 on Child Protection, so at the regional level, the Government of Aceh followed up by stipulating the Qanun Number 11 Year 2008 on Child Protection. The Qanun states that child protection aims to ensure the right for life, grow, develop, and participate optimally as well as humanistic value and dignity, and children get protection from exploitation, violence, and discrimination. Those all protections toward to realize the good quality of children in Aceh, good morality, and wealth. Child protection is conducted through religion, custom, socio-cultural development. It puts forward basic principles, namely anti-discrimination, the child’s needs-response, the right to live, and appreciation. Substantially, the Qanun contains all rights in protecting the child. But there are needs in socializing and optimizing the law enforcer in protecting children. This study found many indicators on the less of child protection in Aceh. Recently, Aceh stands as the third-highest rank province in Sumatera with the number of child violence. Furthermore, children’s sexual harassment becomes the most reported case.